PENILAIAN KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Asri Nur Wahyuni; Fitri Lukiastuti (ECONBANK: Journal of Economics and Banking, 2019)
One consideration of an investor before investing is to look at the company's financial performance. There are several variables that influence the assessment of the company's financial performance, in the proposed research, it will examine the variables of liquidity, solvability, activity and profitability and macroeconomic variables, namely inflation as a moderating variable.The research object is all manufacturing sector companies for 5 years (2013-2017). Data requirements to be analyzed are obtained from the company's financial statements published through IDX and ICMD (Indonesia Capital Market Directory). The analytical tool used is MRA analysis (moderate regression analysis). Based on the results of the analysis, it is known that the influence of company financial statements that reflect the financial performance of manufacturing companies that are increasingly reinforced by inflation as a macroeconomic factor.The results of this study are expected to provide empirical contributions regarding the assessment of the company's financial performance based on financial statement analysis taking into account the impact of inflation that occurs and become the reference basis for investors before investing their capital.